A Systematic Review of the Relationships Between Craving and Smoking Cessation - Wray, Jennifer M. (Oxford University Press, 2013)
INTRODUCTION: Craving is often portrayed as a defining feature of addiction, but the role of craving in the addictive process is controversial. Particularly contentious is the extent to which drug craving predicts subsequent relapse. METHODS: This review synthesizes findings from 62 smoking cessation studies published through December 2011. Eligible studies measured craving for cigarettes in treatment-seeking smokers and related this to subsequent smoking status. The relationships of general craving and cue-specific craving with treatment outcome were examined separately. Further, analyses that related general craving to smoking status were divided into those that used craving data collected before the quit attempt, after the quit attempt, and those that used change in craving over time as a predictor. RESULTS: Results across studies revealed a total of 198 indices of association with 94 (47%) of these being significant. In general, the findings indicated (a) there were only a few cases of significant associations between craving collected as part of cue-reactivity studies and treatment outcome, (b) postquit craving was a stronger predictor of treatment outcome than prequit craving, and (c) several moderators likely influence the relationship between craving and cessation outcome. CONCLUSIONS: The overall results suggest that craving is not a necessary condition of relapse. In addition, inconsistent relationships between craving and treatment outcome call into question the value of craving as a target of treatment and underscore limitations in the prognostic utility of craving.